1982
DOI: 10.1083/jcb.92.3.733
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical coupling in the relaxation of rigor-wave sea urchin sperm flagella.

Abstract: The relaxation (straightening) of flagellar rigor waves, which is known to be induced by micromolar ATP concentrations, was investigated with respect to its dependence on the binding and hydrolysis of ATP. Flagellar rigor waves were formed by the dilution of demembranated, reactivated sea urchin ( Lytechinus pictus) spermatozoa into ATP-free buffer . Relaxation in response to nucleotide was quantitated by measuring G, the mean flagellar bend angle per sperm; this novel assay permitted determination of the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Consistent with previous reports, most isolated respiratory cilia had an intrinsic structural curvature in the nonactivated state, as shown by negative staining on electron microscopic images (Figure 1, G) and cryo-electron microscopic images (Figure 1, H) in the similar manner with some previous reports with light microspopy. [30][31][32][33][34] These results suggest that the axonemal structure in respiratory cilia is asymmetrical, as was found in Chlamydomonas flagella axonemes. 18 …”
Section: Tracking the Motion Of Individual Cilia Through Qds Labelingsupporting
confidence: 69%
“…Consistent with previous reports, most isolated respiratory cilia had an intrinsic structural curvature in the nonactivated state, as shown by negative staining on electron microscopic images (Figure 1, G) and cryo-electron microscopic images (Figure 1, H) in the similar manner with some previous reports with light microspopy. [30][31][32][33][34] These results suggest that the axonemal structure in respiratory cilia is asymmetrical, as was found in Chlamydomonas flagella axonemes. 18 …”
Section: Tracking the Motion Of Individual Cilia Through Qds Labelingsupporting
confidence: 69%
“…To address this issue, we produced axonemes in a relaxed state by exposing them to low concentrations of ATP (<10 μM), as reported previously (22,23). In our protocol, 2 μM ATP caused the smallest average bend angle (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…A possible explanation for this difference is that the axonemal curvature observed in the WT axonemes results from fixation of the axoneme in an active position of the ciliary beating cycle, which can result from strong rigor states of dynein motors (22,23). To address this issue, we produced axonemes in a relaxed state by exposing them to low concentrations of ATP (<10 μM), as reported previously (22,23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymatic studies of dynein (45,47,58) and other ATPases (20,41) have concluded that vanadate does not prevent either the ATP binding or ATP hydrolysis steps of the ATPase cycle. However, an ADP.V complex forms that cannot be released from the enzyme, preventing further rounds of hydrolysis.…”
Section: Outer-arm Conformations In Nonmotile Ciliamentioning
confidence: 99%